Opioid-Related Treatment Disparities Among Medicaid Enrollees in Indiana (Mary Ann Liebert, 2023)
Introduction: Health care disparities based on race/ethnicity and sex can be found in a variety of settings. Our aim is to determine if there are disparities in treatment provided to Indiana Medicaid enrollees who have medically documented opioid use. Study Data and Methods: We used Medicaid reimbursement claims data to extract patients who were diagnosed with opioid use disorder (OUD) or had other medical event related to opioid use between January 2018 and March 2019. We used a two-proportion Z-test to verify the difference in the proportion of treatment provided between population subgroups. The study was approved by the Purdue University Institutional Review Board (2019?118). Study Results: Over the study period, there were 52,994 Indiana Medicaid enrollees diagnosed with OUD or documentation of another opioid related event. Only 5.41% of them received at least one type of treatment service (detoxification, psychosocial, medication assisted treatment, or comprehensive). Discussion: Although Medicaid began covering treatment services for enrollees with an OUD in Indiana at the start of 2018, very few received evidence-based services. Men and White enrollees with an OUD were in general more likely to receive services compared to women and non-White enrollees.